Humanizing the past: a review on the role of facial approximation in museums and its public perception - Vanni, Arianna; Licata, Marta; Fusco, Roberta; Rossetti, Nicol; Picozzi, Mario (Frontiers in Environmental Archaeology, 2025)
Facial approximation in archaeological contexts represents a complex intersection of science, art, and ethics. While these reconstructions offer a unique opportunity to engage the public with the past, they also raise critical concerns regarding accuracy, representation, and the dignity of the deceased. This literature review examines the ethical discourse surrounding facial approximations in museums, emphasizing the need for transparency in their creation and presentation. By integrating anthropology, ethics, and museum studies, we highlight both the potential and the limitations of these estimations. A balanced approach—one that acknowledges interpretative subjectivity while fostering public engagement—can enhance the ethical and scientific integrity of facial approximation practices in archaeological field.